A secreted citrus protease cleaves an outer membrane protein of the Huanglongbing pathogen - Alexander J. McClelland; Bin Hu; Yuantao Xu; Xiaodong Fang; Chunxia Wang; Benjamin L. Koch; Amelia H. Lovelace; Eva Hawara; Yuanchun Wang; Zhiqian Pang; Agustina De Francesco; Suzanne P. van Wier; et al. (Proceedings of the National Academy of Sciences, 2026)
Plants secrete a variety of proteases as a defense response during infection by microbial pathogens. However, the relationship between their catalytic activities and antimicrobial functions remains largely unknown. Particularly, few biologically relevant substrates of these proteases have been identified. Huanglongbing (HLB) has been a major threat to the citrus industry worldwide. The HLB-associated bacterium, “ Candidatus Liberibacter asiaticus” (Las), was previously shown to deploy an inhibitor of papain-like cysteine proteases (PLCPs) to promote disease in citrus. In this study, we identified an outer membrane protein (OMP) of Las, LasOMP1, as a substrate of the citrus PLCP Cs RD21a. LasOMP1 is one of the most highly expressed genes in Las. Cs RD21a cleaves LasOMP1 and produces cleaved peptide products, which could be detected in vitro and in HLB-diseased citrus plants. We found that Cs RD21a targets the N-terminal portion of LasOMP1, potentially at an extracellular loop region. Importantly, transgenic sweet orange overexpressing Cs RD21a showed reduced Las populations and improved plant growth, highlighting that engineering this protease is a promising strategy to enhance HLB resistance in citrus. Together, our work reveals a pathogen-derived substrate of plant PLCPs and suggests bacterial OMPs may be direct targets of plant defense.